Examination of changes in land cover around settlements: The case of Drahna forest sub-district directorate - Durkaya, Ali; Kaptan, Sinan; Durkaya, Birsen; Kaptan, Sinan; Durkaya, Birsen; Durkaya, Ali (International Symposium of Ecology, 2018)
In order to manage forests sustainably, it is necessary to protect, develop and monitor the production capabilities and quality of forest ecosystem, biodiversity, its contribution to the world's carbon cycle, land and water resources and other socio-economic functions. For this reason, it is important to monitor and report the changes occurring in forest ecosystems and to take the necessary precautions in place and on time. In this study, changes occurred in the forest and nonforest areas around settlements within the boundaries of the Drahna Forest Sub-District Directorate during the time period of 40 years between 1967 and 2006 were tried to be introduced with the help of ArcGIS which is one of the Geographic Information Systems (GIS) tools. Material and Methods: Three forest management plans and relevant stand data maps of Drahna Forest Sub-District Directorate, which is affiliated to Ulus Forestry Operation Directorate of Zonguldak Regional Directorate of Forestry, for the periods 1967-1986 (1st Plan Period), 1986-2005 (2nd Plan Period) and 2006-2025 (3rd Plan Period) were examined using ArcGIS version 10.4. The non-digitized 1st and 2nd period stand data maps were digitized and the map belonging to the 3rd plan period was obtained from the related unit in digitized form. Land changes occurred in three affected zones of 0-250, 251-500 and 501-1.000 m, which were created on the basis of settlements of 11 forest villages within the plan unit, were examined in terms of area and time. Results: Within 0-250 m, the normal closed forest area increased by 142,46 ha, and the open forest area decreased by 166,74 ha. The settlement area increased by 87,06 ha, the cutover forest land (OT) increased by 8,89 ha and the agricultural area decreased by 71,69 ha. Within 251-500 m, the normal closed forest area decreased by 421.78 ha and the open forest area decreased by 448.29 ha. While the settlement area increased by 12,12 ha and the OT area increased by 13,32 ha, the agricultural area decreased by 0.13 ha. Within 501-1,000 m, while the normal closed forest area increased by 891.14 ha, the open forest area decreased by 782.45 ha. The settlement area, which had not been shown in the maps in 1967, was measured as 1.49 ha in 2006 after 40 years and while the OT area increased by 13,60 ha, the agriculture area decreased by 119,76 ha. Throughout the affected zones (0-1.000 m), an increase was determined in the normal closed forest areas during the period of 40 years from 1967 to 2006 and a continuous decrease was determined in the open forest area and in agricultural areas. Discussion: Our national forest assets, which are 20.2 million hectares according to the inventory data for the period 1963-1973, reached up to 22.3 million hectares in 2017 by continuing to increase every year. Within the study area, the general forest area (normal + open) decreased by 24,28 ha and 26,51 ha respectively in the affected zones of 0-250 and 251-500 m within the period of 40 years and increased by 108,69 ha within the affected zone of 501-1,000 m. A decrease was determined in the forest area which is around 500 m of the settlement areas. According to the results obtained from the study, it is observed that there was a decrease in agricultural areas and open forests and an increase in normal closed forests.
Keywords: Land cover; GIS; Temporal change; Drahna forest; Forestry management; Drahna ormanı; Orman yönetimi; Coğrafi bilgi sistemi